High throughput direct 3D bioprinting in multiwell plates. (10th March 2021) - Hwang, Henry H; You, Shangting; Ma, Xuanyi; Kwe, Leilani; Victorine, Grace; Lawrence, Natalie; Wan, Xueyi; Shen, Haixu; Zhu, Wei; Chen, Shaochen
Abstract: Advances in three dimensional (3D) bioprinting have enabled the fabrication of sophisticated 3D tissue scaffolds for biological and medical applications, where high speed, high throughput production in well plates is a critical need. Here, we present an integrated 3D bioprinting platform based on microscale continuous optical printing, capable of high throughput in situ rapid fabrication of complex 3D biomedical samples in multiwell plate formats for subsequent culture and analysis. Our high throughput 3D bioprinter (HT-3DP) was used to showcase constructs of varying spatial geometries of biomimetic significance, tunable mechanical properties, as well as reproducibility. Live hepatocellular carcinoma 3D tissue scaffolds were fabricated in situ in multiwell plates, after which a functional drug response assay against the chemotherapy drug doxorubicin was performed. Dual cell-type populations involving both live hepatocellular carcinoma as well as human umbilical vein endothelial cells were also printed to demonstrate dual-tissue fabrication capability. This work demonstrates a significant advancement in that the production rate of 3D bioprinted tissue scaffolds with controllable spatial architectures and mechanical properties can now be done on a high throughput scale, enabling rapid generation of in vitro 3D tissue models within conventional multiwell cell culture plates for high throughput preclinical drug screening and disease modeling.